A case for using both direct and indirect benchmarking to compare university performance metrics. Issue 12 (2nd December 2019) - Harris, W. E.; Langan, A. M.; Barrett, N.; Jack, K.; Wibberley, C.; Hamshire, C.
ABSTRACT: Benchmarking is used in higher education as a means to improve and compare performance. Comparative metric benchmarks may take two forms, based on direct standardization (DS) or indirect standardization (IS). DS can be used to measure variation in performance between institutions, controlling for intrinsic differences at each institution (e.g. controlling for differences in student typologies). IS can be used to measure variation in performance between institutions, compared to average performance overall. Typically, IS has been used to moderate educational output metrics, such as student qualification and satisfaction. We contrast the two approaches with an example dataset for three years of nursing student completion rates from nine institutions. Profiles of benchmarks and actual performance indicated that both approaches provide valuable and different perspectives to comparisons of institutional performance. We discuss the potential merits to stakeholders of each approach and conclude that decision-making can be best informed using both benchmark methods.